Berberine Modulates Gut Microbiota and Reduces Insulin Resistance via the TLR4 Signaling Pathway - Liu, Dan; Zhang, Yiyi; Liu, Yunhui; Hou, Liqiong; Li, Sheyu; Tian, Haoming; Zhao, Tieyun (Experimental and Clinical Endocrinology & Diabetes, 2018)
Berberine, a natural compound extracted from several Chinese herbs including Coptis chinensis, has been shown to have anti-obesity effects and prevents insulin resistance in high-fat diet (HFD)-fed obese rats by modulating the gut microbiota; however, the molecular mechanisms underlying these activities remain unknown. We investigated the effects of berberine on obesity and insulin resistance by examining the lipopolysaccharide (LPS)/toll-like receptor 4 (TLR4)/tumor necrosis factor (TNF)-α signaling pathway in livers of HFD-fed obese rats. Our results showed that 8-week berberine (200 mg/kg) treatment significantly reduced fasting blood glucose, triglyceride, low-density lipoprotein-cholesterol and insulin resistance in HFD-fed obese rats. However, berberine had no significant effects on body weight, visceral fat mass or the visceral fat to body weight ratio. Berberine also attenuated HFD-induced hepatic steatosis. A prolonged HFD altered the gut microbiota composition by reducing protective bacteria like Bifidobacterium and increasing gram negative bacteria like Escherichia coli, which resulted in increased LPS release into plasma. Berberine reversed these effects and inhibited LPS-induced TLR4/TNF-α activation, resulting in increased insulin receptor and insulin receptor substrate-1 expression in the liver. These findings suggested that berberine may reduce insulin resistance, at least in part by modulating the gut microbiota along with inhibiting LPS/TLR4/TNF-α signaling in the liver.
Keywords: berberine; gut microbiota; lipopolysaccharide; insulin resistance; TLR4